Adsorption of Some Transition Metal Ions [Cu(II), Fe(III), Cr(III) and Au(III)] onto Lignite-Based Activated Carbons Modified by Oxidation - Paunka St. Vassileva; Albena K. Detcheva (Adsorption Science & Technology)
The main purpose of the present work was to study the adsorption of some transition metal ions from aqueous solution via a novel porous material obtained from Bulgarian lignite (Chukurovo deposit) and its oxidized modifications. The adsorption of Cu(II), Fe(III), Cr(III) and Au(III) ions was investigated using batch methods to study solutions with different concentrations and acidities. It was found that the adsorption process was affected significantly by the pH value of the aqueous solution. Treatment of the equilibrium data using the linear Langmuir, Freundlich and Dubinin-Radushkevich models allowed the maximum adsorption capacities to be calculated. The uptake of Au(III) ions was almost 100% for the three adsorbents investigated, being greater than 300 mg/ℓ and independent of the pH over the pH range studied. The initial activated carbon proved to be the most suitable for the selective adsorption of Au(III) ions from aqueous solutions in the presence of other transition metal ions, while its oxidized modification Ch-P exhibited an enhanced adsorption efficiency towards transition metals.